BANKING SECTOR OF THE SAMARA REGION: HISTORY OF FORMATION, CURRENT STATE, DEVELOPMENT PROSPECTS - M. Barbarskуa; L. Yegorova; E. Lazareva (Вестник университета, 2019)
The article is devoted to the study of the formation of the banking sector in the Samara region. The stages of development of the banking organizations of the region are presented, special attention is paid to the performance indicators of banking organizations at the present time. The structure of financial resources of credit institutions is studied, a review of performance indicators of banking organizations, such as the value of net assets, the amount of financial result, the level of return on equity. Prospects for the development of the banking sector of the Samara region are considered, they are more connected with the specifics of the activities of regional banks.